(untitled) (The Review of Diabetic Studies, 2024)
Eye injuries represent one of the most preventable yet vision-threatening emergencies globally, accounting for significant visual morbidity and long-term disability across all age groups. The misuse or overuse of antimicrobials in the management of ocular trauma remains a major contributor to antimicrobial resistance, nosocomial infection risk, and unnecessary economic burden. In the context of modern healthcare, optimizing antimicrobial use in eye injuries demands an integrated, multidisciplinary framework involving ophthalmologists, pharmacists, nurses, and central sterilization specialists. Ophthalmologists lead diagnosis, surgical management, and empirical antibiotic selection, pharmacists ensure antimicrobial stewardship and resistance surveillance, nurses maintain strict asepsis and medication compliance, while central sterilization teams safeguard instrument sterility and prevent cross-infection in surgical and outpatient settings. This paper provides a comprehensive review of antimicrobial optimization in ocular trauma through a multidisciplinary lens. It analyzes global and regional data, particularly within Saudi Arabia’s Vision 2030 healthcare transformation framework, and explores how integrated collaboration can reduce resistance patterns, improve clinical outcomes, and enhance patient safety.